PERAN PUSTAKAWAN DAN PEMANFAATAN KOLEKSI BAGI PEMUSTAKA LAYANAN REFERENSI DINAS KEARSIPAN DANPERPUSTAKAANPROVINSI SUMATERA BARAT - Friona, Mifthahul Khairi (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
The aim of this research is research is to find out and the role of librarians and the utilization of collections for reference service users at the Archives and Libraries Office of West Sumatra Province. This research uses qualitative methods by using observation, interviews, and documentation to obtain primary data, as well as documentation to obtain secondary data. Based on the result, it can be it can be seen that the reference librarian of the West Sumatra Provincial Archives and Libraries Office in meeting the information needs of the library users has played a role in helping users who have difficulty finding the desired collection, besides that the reference librarian also directs the user to find the collection on the shelf and guides the user to search for printed collections by doing it together to find the collection needed. The innovations made by the reference librarian of the West Sumatra Provincial Archives and Libraries Office are such as carrying out user education activities which include direct guidance, which includes collection search guidance, guidance on using OPAC, and information search guidance. Librarians also provide reference cards for librarians who have not found the reference sources they need.